Motility Response to Colonic Distention is Increased in Post-infectious Irritable Bowel Syndrome (PI-IBS) - Kanazawa, Motoyori (Neurogastroenterol Motil, 2014)
BACKGROUND: Acute intestinal infection leads to persistent intestinal smooth muscle hypercontractility and pain hypersensitivity after resolution of the infection in animal models. We investigated whether post-infectious irritable bowel syndrome (PI-IBS) is associated with abnormalities in phasic contractions of the colon, smooth muscle tone and pain sensitivity compared to non-PI-IBS (NI-IBS) or healthy controls (HC). METHODS: 218 Rome III positive IBS patients and 43 healthy controls participated. IBS patients were designated PI-IBS if their IBS symptoms began following an episode of gastroenteritis characterized by 2 or more of: fever, vomiting, or diarrhea. Pain threshold to phasic distentions of the descending colon was assessed using a barostat. Colonic motility was assessed with the barostat bag minimally inflated to the individual operating pressure (IOP), at 20 mmHg above the IOP, and following a test meal. IBS symptom severity and psychological symptoms were assessed by the IBS Severity Scale (IBS-SS) and the Brief Symptom Inventory-18 (BSI-18). KEY RESULTS: Twenty-two (10.1%) met criteria for PI-IBS. Both IBS and HC groups showed a significant increase in motility index during intraluminal distention and following meals. The magnitude of the response to distention above (orad to) the balloon was significantly greater in PI-IBS compared with NI-IBS (p<0.05) or HC (p<0.01). Differences between PI-IBS and NI-IBS were not significant for IBS symptom severity, pain threshold, barostat bag volumes, or any psychological score on the BSI-18. CONCLUSIONS & INFERENCES: Patients with PI-IBS have greater colonic hypercontractility than NI-IBS. We speculate that sustained mild mucosal inflammation may cause this colonic irritability.